An unusual case report of metastatic periampullary carcinoma - Shah, Suryalok Pratap; Pandit, Shahbaz Ahmad; Pandey, Alok Kumar; Kumar, Supreet; Gautam, Rahul; Bhalerao, Aishwarya; Tandon, Vivek; Govil, Deepak (International Surgery Journal, 2024)
Pancreatic cancers usually metastasize through the lymphoid system to organs such as the lung, liver, bone and spleen. Ovarian metastasis in pancreatic cancers is extremely rare, hence, it is difficult to distinguish between primary and metastatic ovarian tumors, especially in tumors with a primary source from the GIT & Hepatobiliary system. We present the case of a periampullary carcinoma with ovarian metastasis in a middle-aged female who presented with complaints of abdominal pain, constipation, yellowish discoloration of eyes and dark colored urine along with loss of appetite and weight loss for a duration of 6 to 8 weeks. Radiological examination revealed right adnexal lesion and nodular thickening along periampullary region. ERCP guided biopsy of the growth in periampullary region revealed moderately differentiated adenocarcinoma. She underwent pancreatico-duodenectomy with bilateral salpingo-oophorectomy. The histopathological examination revealed invasive carcinoma in both the ovaries, and moderately differentiated adenocarcinoma in periampullary and intra-ampullary region. As per the findings in previous studies, bilateral ovarian tumors of any size, or a unilateral tumor less than 10 cm likely represents metastatic disease rather than primary ovarian tumor. The rarity of co-presentation of pancreatic and adnexal mass makes the diagnosis tough however it is important to differentiate between primary ovarian mucinous cancers and ovarian metastasis from primaries in GIT for further treatment and follow up.